2018
DOI: 10.3389/fphar.2018.00437
|View full text |Cite
|
Sign up to set email alerts
|

Bushen Huoxue Recipe Alleviates Implantation Loss in Mice by Enhancing Estrogen–Progesterone Signals and Promoting Decidual Angiogenesis Through FGF2 During Early Pregnancy

Abstract: Bushen Huoxue recipe (BSHXR) is a classic Chinese herbal prescription for nourishing the kidney and activating blood circulation. It consists of six herbs: Astragali radix, Angelicae sinensis radix, Ligustici Chuanxiong Rhizoma, Cuscutae semen, Taxilli Herba, and Dipsaci Radix, and the main active constituents of BSHXR are ferulic acid, calycosin-7-glucopyranoside, hyperoside, quercitrin, and asperosaponin VI. In clinical practice, BSHXR is traditionally used to treat failed pregnancy and its complications. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…EBZYD combined with acupuncture treatment showed more pinopodes and thicker endometrium than EBZYD or acupuncture administration. The development and maturation of the vascular network are essential for the successful development of the placenta and normal embryonic growth [ 31 ]. VEGF is a key angiogenic modulator, regulating uterine angiogenesis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…EBZYD combined with acupuncture treatment showed more pinopodes and thicker endometrium than EBZYD or acupuncture administration. The development and maturation of the vascular network are essential for the successful development of the placenta and normal embryonic growth [ 31 ]. VEGF is a key angiogenic modulator, regulating uterine angiogenesis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…BuShen HuoXue decoction (BSHXD) is an efficacious prescription to prevent miscarriage in URSA and assist reproduction [ 13 ]. Previous studies of its mechanism in rats have provided a theoretical and practical reference for the comprehensive roles of BSHXD in angiogenesis, hormone management, endometrial receptivity, and reproductive outcomes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, TA can be mainly attributed to the deficiency of the viscera especially the deficiency of the kidney according to the theories of traditional Chinese medicine (TCM). Herbs like Cuscutae Semen (Tusizi in Chinese), Herba Taxilli (Sangjisheng in Chinese), Dipsaci Radix (Xuduan in Chinese), and Astragali Radix (Huangqi in Chinese) are used to treat TA for their functions of replenishing the kidney essence (Shen Jing in Chinese) and nourishing the liver [17,18]. Zeng et al [19] and Li's [20] researches based on a data mining method have shown that Cuscutae Semen and Herba Taxilli were frequently prescribed for TA treatment and were always used in combination as an herb pair, indicating the key role of these two herbs in TA treatment and the representative value for other akin herbs to explore the potential mechanisms of action on TA treatment.…”
Section: Introductionmentioning
confidence: 99%